Author Correction: Structure and mechanogating mechanism of the Piezo1 channel. (8th November 2018) - Zhao, Qiancheng; Zhou, Heng; Chi, Shaopeng; Wang, Yanfeng; Wang, Jianhua; Geng, Jie; Wu, Kun; Liu, Wenhao; Zhang, Tingxin; Dong, Meng-Qiu; Wang, Jiawei; Li, Xueming; et al.
In Extended Data Fig. 9a of this Article, the bottom micrographs of mPiezo1-ΔL3-4-IRES-GFP and mPiezo1-ΔL7-8-IRES-GFP (labelled 'permeabilized') are inadvertently the same images. The corrected figure panels are shown in the accompanying Amendment.